2018
DOI: 10.1680/jadcr.17.00041
|View full text |Cite
|
Sign up to set email alerts
|

Influence of triethanolamine on cement pastes at early age of hydration

Abstract: Activation is often associated with the favoured hydration of particular cementitious phases, which can be induced by complexation mechanisms. However, the dispersion state of pastes with admixtures may also influence hydration rates. The aim of this paper is to highlight the correlation between mesostructural organisation and chemical reactivity of cement pastes with an additive. The affinity of triethanolamine (TEA), an activator molecule, with cement grains was assessed by measurement of total organic carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A systematic investigation of the effect of TEA on cement hydration can be backdated to the 1970s, during which a series of papers from Ramachandran 3–6 and Ciach et al 7–11 were published regarding the effect of TEA on the hydration process of different mineralogical phases in cement and the corresponding morphological change of the hydration products. Since then, many meaningful pieces of the literature have been published regarding the interaction of TEA with cement in different aspects, such as on cement hydration, 12–15 setting, 13,16 strength, 17,18 microstructure after hardening, 16 rheological performance 19,20 . It is widely accepted that the addition of TEA accelerates the C 3 A hydration and the transformation of ettringite (AFt) to monosulfate (AFm), and retards the tricalcium silicate (C 3 S) hydration 12,16 .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic investigation of the effect of TEA on cement hydration can be backdated to the 1970s, during which a series of papers from Ramachandran 3–6 and Ciach et al 7–11 were published regarding the effect of TEA on the hydration process of different mineralogical phases in cement and the corresponding morphological change of the hydration products. Since then, many meaningful pieces of the literature have been published regarding the interaction of TEA with cement in different aspects, such as on cement hydration, 12–15 setting, 13,16 strength, 17,18 microstructure after hardening, 16 rheological performance 19,20 . It is widely accepted that the addition of TEA accelerates the C 3 A hydration and the transformation of ettringite (AFt) to monosulfate (AFm), and retards the tricalcium silicate (C 3 S) hydration 12,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that TEA affects not only the hydration of the main clinker phases but also the dissolution of sulfate carriers 13,17 . Recchi et al 18 reported a substantial influence of the type and quantity of single sulfate carriers on the workability and compressive strength of TEA-added mortars.…”
Section: Accepted Articlementioning
confidence: 99%
“…TEA, conventionally used as a grinding aid for cement clinker as well as an accelerator to compensate for the retarding effect of some superplasticizers [25], might also be used as a setting accelerator in additive manufacturing [27]. The effect of TEA on the hydration of ordinary Portland cement-based materials has been discussed by [27][28][29][30][31][32][33][34]. While the precise mechanism is still under debate, there is a general agreement that TEA accelerates the hydration of the aluminate-containing phases tricalcium aluminate (C 3 A) and brownmillerite (C 4 AF) and consequently reduces the initial setting time while delaying the hydration of alite [27,29,33,34].…”
Section: Theoretical Frameworkmentioning
confidence: 99%